Corporate social responsibility (CSR) theory and practice in Pakistan - Hameed, Syed Kamran (2010)
This master thesis is dealing with the Corporate Social Responsibility (CSR) and its awareness in Pakistani companies. The objective is to see how different companies in Pakitan (multinationals and domestic) view the CSR concept in their strategy.